Aligned silver nanowires as transparent conductive electrodes for flexible optoelectronic devices. Issue 47 (14th November 2016) - Wu, Fan; Li, Zidong; Ye, Feng; Zhao, Xiaoli; Zhang, Tong; Yang, Xiaoniu
Abstract : A novel and facile strategy of restricting the nanowire orientation and thus improving the optical and electrical performance of the AgNW networks is proposed. Abstract : Silver nanowire (AgNW) networks, which are promising alternatives to indium tin oxide (ITO) as transparent conductive electrodes, have been a recent focus in the application of flexible optoelectronic devices. For the purpose of improving the optical and electrical performance of the network, herein, a novel "capillary-assisted fluidic assembly" technique is proposed, which simply involves a one-step solution process. Using this technique, numerous individual nanowires are well aligned over a large area with controlled density. In addition, the network with aligned AgNWs is consequently constructed, possessing remarkably improved optical and electrical performance ( R s = 16.6 Ω sq −1, T @550nm = 92.7%) as compared to that with random AgNWs. Large-scale polymer solar cells are taken as an example to demonstrate the efficacy of this technique and the device based on aligned AgNWs exhibit a power conversion efficiency of 6.01%, which is much higher than that based on random AgNWs. Notably, this is the highest efficiency reported to date using AgNW electrodes with a device area of 1.0 cm 2 . It is further found that the aligned AgNW networks exhibit significantly better mechanical stability than the brittle ITO films. This technique, which is compatible with roll-to-roll processes, shows promising potential in the continuous fabrication of large-area flexible optoelectronic devices.